To solve the equation 3/8(2x+16) - 2 = 13, we need to isolate the variable x.
First, let's distribute 3/8 to 2x+16:
(3/8)(2x+16) - 2 = 13
(3/8) * 2x + (3/8) * 16 - 2 = 13
(6/8)x + 48/8 - 2 = 13
Now, simplify the expression:
(6/8)x + 6 - 2 = 13
(6/8)x + 4 = 13
Next, subtract 4 from both sides of the equation:
(6/8)x + 4 - 4 = 13 - 4
(6/8)x = 9
Now, simplify the equation by canceling out the common factors:
(6/8)x = 9
(3/4)x = 9
To eliminate the fraction, we can multiply both sides of the equation by the reciprocal of (3/4), which is (4/3):
(4/3) * (3/4)x = (4/3) * 9
(1)x = 12
Now, x = 12 is the solution to the equation.
3/8(2x+16)−2=13
1 answer